2007
DOI: 10.1063/1.2713935
|View full text |Cite
|
Sign up to set email alerts
|

Defect induced low temperature ferromagnetism in Zn1−xCoxO films

Abstract: We present a detailed study on the structural, magnetic, and optical properties, as well as the electronic structure of epitaxial Co-doped ZnO films prepared by magnetron sputtering. Different preparation conditions were implemented in order to control the concentration of oxygen vacancies in the ZnO host lattice. Magnetization measurements indicate ferromagnetic behavior at low temperature for samples prepared at oxygen-poor conditions whereas the samples prepared at oxygen-rich conditions show extremely smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
25
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 45 publications
6
25
0
Order By: Relevance
“…The spectrum agrees well with those from Krishnamurthy et al [33] and Chang et al [34] measured at undoped ZnO. No visible change of the spectral features between 530 and 544 eV due to the presence of oxygen vacancies [16], [33], [34] can be observed, which leads to the conclusion that an effective introduction of oxygen vacancies has not been achieved. XMCD measurements by Tietze et al [31] also showed that oxygen itself is not the origin of ferromagnetism in Co-doped ZnO.…”
Section: Methodssupporting
confidence: 80%
See 1 more Smart Citation
“…The spectrum agrees well with those from Krishnamurthy et al [33] and Chang et al [34] measured at undoped ZnO. No visible change of the spectral features between 530 and 544 eV due to the presence of oxygen vacancies [16], [33], [34] can be observed, which leads to the conclusion that an effective introduction of oxygen vacancies has not been achieved. XMCD measurements by Tietze et al [31] also showed that oxygen itself is not the origin of ferromagnetism in Co-doped ZnO.…”
Section: Methodssupporting
confidence: 80%
“…The interpretation is complicated due to spreading results, as not only ferromagnetism, but also paramagnetism [10], [11] and antiferromagnetism [12] were found. The reports on ferromagnetic behavior range from strong RT ferromagnetism [13]- [15] to weak ferromagnetism only at low temperatures [16], [17]. Several groups even found ferromagnetic behavior with a superconducting quantum interference device (SQUID), while X-ray magnetic circular dichroism (XMCD) showed paramagnetic behavior of the Co atoms [18], [19].…”
mentioning
confidence: 99%
“…2,[32][33][34] A strong correlation has been established between vacuum annealing of samples and ferromagnetism in films. This has been reported in Zn 1-x Co x O, 3,11,[14][15][16]34,35 Zn 1-x Mn x O, 36 ZnO, 36 TiO 2 , 12,13 and HfO 2 . 10 In one case, 15 cycling between ferromagnetic and non-magnetic states by vacuum or air annealing was clearly demonstrated.…”
Section: Thin Film Experimental Workmentioning
confidence: 92%
“…Further more, Dietl and Sato predicted that above room-temperature ferromagnetism could be realized by doping a few percentages of Co or Mn magnetic ions [6,7]. Until now, much attention has been paid to the magnetic properties of ZnO-based DMS materials fabricated by a variety of method [8][9][10][11][12]. However, the magnetic properties still remain an issue since the observed magnetism ranging from paramagnetic, spinglass and antiferromagnetic behavior to ferromagnetism below or even at high temperature [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 95%